2017
DOI: 10.14198/jhse.2017.122.03
|View full text |Cite
|
Sign up to set email alerts
|

Allometric scaling of body mass in running economy data: An important consideration in modeling marathon performance

Abstract: The purpose of this study was to compare metabolic variables during submaximal running as predictors of marathon performance. Running economy (RE) and respiratory exchange ratio (RER) data were gathered during a 30 min incremental treadmill run completed within 2 weeks prior to running a 42.2-km marathon. Paces during the treadmill run progressed every 5 min from 75-100% of 10-km race velocity. Variables at each stage were analyzed as predictors of relative marathon performance (RMP) in competitive (COMP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is common to report E c per kg of body mass ( Shaw, Ingham & Folland, 2018 ); however, the relationship between body mass and oxygen uptake does not increase proportionately and therefore body mass should be scaled allometrically. As in a previous study, body mass was raised to the power of 0.75 (kcal kg −0.75 km −1 ) ( Lundstrom et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is common to report E c per kg of body mass ( Shaw, Ingham & Folland, 2018 ); however, the relationship between body mass and oxygen uptake does not increase proportionately and therefore body mass should be scaled allometrically. As in a previous study, body mass was raised to the power of 0.75 (kcal kg −0.75 km −1 ) ( Lundstrom et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…It was also measured as the energy cost of running, as previous studies recommended this as the primary measurement of running economy ( Shaw, Ingham & Folland, 2014 ; Shaw et al, 2015 ). Moreover, as previous work indicated that the relationship between body mass and oxygen uptake did not increase proportionately ( Lundstrom et al, 2017 ), body mass was scaled allometrically and energy running cost (E c ) was expressed in kcal kg −0.75 km −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The methodology for modeling competitive activity has been widely developed in cyclic sports: in athletics (Dobrynskaya & Kozlova, 2013;Morais et al, 2014;Lundstrom et al, 2017;Yang et al, 2020); in swimming (Barbosa et al, 2010;Platonov, 2011;Skirenya, 2009).…”
Section: Introductionmentioning
confidence: 99%